Expression analysis of six chromatin and remodeling complex genes (SWR1) in chickpea in different tissues and during heat stress - Chidambaranathan, Parameswaran; Jagannadham, Prasanth Tej Kumar; Satheesh, Viswanathan; Jain, Pradeep Kumar; Srinivasan, Ramamurthy (The Indian Journal of Genetics and Plant Breeding, 2016)
Nucleosome responds to heat stress through histone H2AZ variants. Based on homology searches, we have identified seven genes from the chickpea genome which are homologous to chromatin remodeling complexes (SWR1) in Arabidopsis. Chickpea homologs of PIE (Photoperiod independent early flowering 1), ARP6 (Actin related protein), two SEF (Serrated leaf and early flowering) and three H2AZs (histone 2A variant-Z, a thermosensor in plants) genes were analyzed for expression in chickpea under heat stress and in five different tissues. Expression analysis of these genes during heat stress at pod development stage showed only PIE1 gene was upregulated and heat stress at seedling stage resulted in significant down regulation. Tissue specific expression analysis showed that the expression of PIE1 and SEF was relatively higher in root, flower, pod wall, and grain tissues as compared to that in shoots. Thus, CarPIE1 gene might play an important role in chromatin remodeling complexes during heat stress in chickpea and all the three histone CarH2AZ variants can be good candidate genes for the characterization of basic processes of gene responsiveness in chickpea.